2022
DOI: 10.1111/1346-8138.16593
|View full text |Cite
|
Sign up to set email alerts
|

Trends in prescriptions of oral medications for psoriasis: A single‐center retrospective study

Abstract: Systemic therapy for psoriasis has changed markedly with the advent of biologics. Various studies have provided real-world evidence of their efficacy, adverse reactions, and continuation rates.The development of oral anti-psoriatic drugs has been relatively slow, and conventional oral drugs have long been used. Etretinate was first approved for use in psoriasis in Japan in 1985, followed by cyclosporine in 1992. Methotrexate has been the most frequently used systemic treatment globally since the 1970s 1 ; howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…An increase in prescription of apremilast among oral PsO drugs (mainly because of its improved safety profile) was shown in a single‐center study 29 and a similar trend was also reported in an epidemiological survey of PsO patients in the Japanese Society for Psoriasis Research 30 . Apremilast, with its convenient oral administration and anti‐inflammatory effect but not immunosuppressive mode of action, favorable safety profile, as well as no requirement for laboratory monitoring, offers a unique therapeutic option for patients with PsO and/or PsA 2 …”
Section: Discussionmentioning
confidence: 97%
“…An increase in prescription of apremilast among oral PsO drugs (mainly because of its improved safety profile) was shown in a single‐center study 29 and a similar trend was also reported in an epidemiological survey of PsO patients in the Japanese Society for Psoriasis Research 30 . Apremilast, with its convenient oral administration and anti‐inflammatory effect but not immunosuppressive mode of action, favorable safety profile, as well as no requirement for laboratory monitoring, offers a unique therapeutic option for patients with PsO and/or PsA 2 …”
Section: Discussionmentioning
confidence: 97%